2014 IEEE International Conference on Robotics and Automation (ICRA) 2014
DOI: 10.1109/icra.2014.6906959
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of effect of fingertip stiffness on friction while grasping an object

Abstract: Abstract-In this study, we experimentally investigated the effect of robot fingertip stiffness on friction during grasping of an object. To make robots more human-friendly, robotic hands with soft surfaces have been developed. A soft fingertip, i.e., one with low stiffness, is considered desirable because it produces high friction. However, in our experiments, we were able to obtain high friction from a stiff fingertip under a certain condition. We initially investigated the maximum resistible force when solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 18 publications
(34 reference statements)
3
19
3
Order By: Relevance
“…15. These results correspond to our previous results, which showed that stiffer fingertips have a higher resistible force (frictional force) [11], [12].…”
Section: B Results and Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…15. These results correspond to our previous results, which showed that stiffer fingertips have a higher resistible force (frictional force) [11], [12].…”
Section: B Results and Discussionsupporting
confidence: 81%
“…Watanabe et al [10], [11], [12] investigated the effects of fingertip stiffness on the grasping stability by performing experiments. These studies focused on the contact between rigid objects and soft fingers.…”
Section: A Related Workmentioning
confidence: 99%
“…This made it possible to see the effect of fingertip stiffness more clearly. We also investigated the effect of curvature of the contact surface, which was not investigated in depth in [11]. The main findings are as follows.…”
mentioning
confidence: 99%
“…We include in the definition of this term the effect of fingertip deformation. In contrast to our previous study [11], cylindrical fingertips with flat surfaces were used in this study so that the contact area would remain the same when there was no tangential/shearing force. This made it possible to see the effect of fingertip stiffness more clearly.…”
mentioning
confidence: 99%
“…In other words, the pushing distance/force at the danger area starting point is the guaranteed maximum (grasping) force that can avoid fracture. In addition, a phase change from Phase 1 to Phase 2 indicated an alteration in the tofu (it became hard), and there have been reports that a harder contact area can produce larger frictional forces when contacting soft materials [18,19]. Therefore, easier grasping can be expected compared to previous phases.…”
Section: Danger Area Starting Point For Avoiding Fracture and Delmentioning
confidence: 99%